Desmoteplase in acute massive pulmonary thromboembolism - Tebbe, Ulrich; Bramlage, Peter; Graf, Andreas; Lechleitner, Peter; Bode, Christoph; Riess, Friedrich-Christian; Clemens, Norbert; Al-Rawi, Yasir; Konstantinides, Stavros; Goldhaber, Samuel Z. (Thrombosis and Haemostasis, 2009)
Alteplase is standard therapy for patients with acute, massive pulmonary embolism. The novel plasminogen activator desmoteplase displays high fibrin specificity and selectivity for fibrin-bound plasminogen. In a preclinical model desmoteplase was twice as potent with a shorter lysis time and lower reocclusion rate. We conducted a phase II study comparing 125, 180, and 250 μg/kg bodyweight desmoteplase with 100 mg alteplase. Efficacy criteria were total pulmonary resistance (TPR), mean pulmonary artery pressure (mPAP), and Miller Index. Intention to treat analysis of 34 patients. The reduction of TPR after 24 hours was comparable between desmoteplase 180 μg/kg and alteplase (-48.0 ± 22.4 vs. –50.4 ± 16.3%; p = n.s. vs. alteplase; p = 0.0002 and p<0.0001 vs. baseline). The greatest effect was achieved with desmoteplase 250 μg/kg (-56.0 ± 29.4%; p = n.s. vs. alteplase, p = 0.0055 vs. baseline). Two hours after treatment PAP was reduced by 27.9 (p = 0.0004 vs. baseline) and 30.4% (p = 0.015 vs. baseline) with the higher doses of desmoteplase and 29.6% with alteplase (p = 0.0006 vs. baseline). Further PAP reduction after 6 hours was most pronounced in the desmoteplase 250 μg/kg group (-40.1 ± 18.0%; p = 0.0028 vs. baseline). The reduction of the Miller Index was greatest using desmoteplase 250 μg/kg (-35.0 ± 21.7%; p = 0.011 vs. baseline), and alteplase (-41.6 ± 27.2%; p = 0.0003 vs. baseline). Safety did not differ among the 4 groups. The study results suggest that desmoteplase at doses of 180 and 250 μg/kg had similar or greater efficacy compared to alteplase 100 mg. Onset of action was faster, safety was comparable.
Keywords: Desmoteplase; alteplase; t-PA; massive pulmonary embolism; lysis; Miller Index; pulmonary artery pressure; total pulmonary resistance